1999
DOI: 10.2172/4852
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of In Situ Cleanable HEPA Filters

Abstract: DISCLAIMERThis report was prepared as an account of work sponsoredby an agency of the UnitedStates Government.Neither the United States Governmentnor any agency thereof,nor any of their employees, makes any warranty, express or impliecl or assumes any legal liability or respondility for the accuracy, completeness,or usefulnessof any information apparatus, product, or process disclosed,or representsthat its use would not infringeprivately owned rights.Referencehereinto any specificcommeraal product, process,or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The results of those tests are reported in document WSRC-TR-98-00382 issued in October of 1998. 1 The findings suggested that a full-scale HEPA filter utilizing porous metal media was feasible.…”
Section: Executive Summarymentioning
confidence: 99%
“…The results of those tests are reported in document WSRC-TR-98-00382 issued in October of 1998. 1 The findings suggested that a full-scale HEPA filter utilizing porous metal media was feasible.…”
Section: Executive Summarymentioning
confidence: 99%
“…(10) From the analysis one could determine what analytes were collecting on the filter media from the simulant. These materials (and atmospheric dust), neglecting the radioactive constituents, are believed to be responsible for plugging the existing HEPA filters in the HLW tanks.…”
Section: Test Solutionsmentioning
confidence: 99%
“…Proof of principle for an in situ cleanable HEPA filter was a success with the lab scale filters, which led to the full-scale single element work with the ceramic and sintered metal filters. (2) Through the Tanks Focus area, this technology was shared with other locations such Idaho National Engineering Laboratory (INEL), West Valley and Lawrence Livermore National Laboratory (LLNL). At INEEL, simulated Calcine transfer testing was conducted using small-scale ceramic filters with success.…”
mentioning
confidence: 99%
“…Savannah River Site has been experimenting with washable ceramic HEPA filters. 4,5 Further studies on these filters would need to be checked for flow capacity, amount of rinse solution produced, and plugging problems with the acidic scrubber off-gas.…”
Section: Hepa Filter Disposalmentioning
confidence: 99%